Searching for new physics in WW and single-W events - Einhaus Ulrich; List Jenny; Reichenbach Leonhard; Silva Andre Filipe (EPJ Web of Conferences)
Pair-production and single-production of W bosons provide many opportunities to look for new physics via precision measurements, for instance via scrutinising the involved triple-gauge vertices or by measuring CKM matrix elements in an environment very complementary to B hadron decays. This contribution presents the ongoing work based on full simulation of the ILD concept, exploiting the O(108) W bosons produced during the 250 GeV stage of the ILC, as well as the CLD concept proposed for the FCC-ee. The projections, which also contribute to two focus topics of the current ECFA study on future Higgs/Top/Electroweak factories, promise improvements of the measurement precision of TGCs and the CKM matrix, respectively, of one to two orders of magnitude with respects to LEP.